The Impact of a Vision Intervention on Translation and Interpretation Students’ L2 Motivation - Carcamo, Benjamin; Carmona, Carmen (Íkala, Revista de Lenguaje y Cultura, 2023)
Visionary teaching interventions have had a positive impact on developing and strengthening students’ ideal L2 self and motivated behavior. However, research on the effects of this kind of intervention on the motivation of translation and interpretation students is scarce. Using a mixed methods approach, the study aimed to evaluate the impact of a semester-long intervention, focused on translation and interpretation students’ future professional careers, on their motivation, intended effort, and willingness to communicate. The participants were translation and interpretation students with a B1 level of English, who were divided in two groups for the study. The treatment group received a vision intervention (N=14) whereas the control group (N=14) did not. To measure the differences in motivation before and after the intervention, a questionnaire was used. Additionally, a semi-structured interview was used to explore in greater depth the students’ perceptions of the experience. The results of this study reveal that visionary teaching increased both ideal L2 self and intended effort of students. Furthermore, it showed that the intervention was memorable for students and that it benefited them in establishing a future L2 professional vision as well as outlining the steps to achieve it. Our findings suggest the importance of including visionary teaching in translation and interpretation programs so that students can become motivated and involved in their future professional paths.